Social contracts and occupational health and safety disclosure: evidence from companies in Indonesia - Abidah Dwi Rahmi Satiti; Djoko Suhardjanto; Wahyu Widarjo; Setianingtyas Honggowati (Cogent Business & Management)
This study presents an analysis of the impact of social contracts on occupational health and safety (OHS) disclosure. The novelty of this study lies in examining the influence of social contracts on OHS disclosure using the perspective of Social Contract Theory, which has not been found in previous studies. Social Contract Theory is operationalized into variables such as job termination ratio, sales target achievement ratio, company fines, debt payment timeliness ratio, and insurance costs. The research sample includes 110 companies at high risk for workplace accidents and occupational diseases listed on the Indonesia Stock Exchange from 2016–2022, totaling 259 observations. The results show that the company fines ratio, debt payment timeliness, and insurance costs positively influence OHS disclosure. However, the job termination ratio and sales target achievement ratio do not affect OHS disclosure. This article contributes to the literature by providing empirical evidence that social contracts influence OHS disclosure, a previously unexplored area. It also contributes to accounting practice by suggesting that companies and stakeholders pay attention to social contracts that can encourage companies to enhance their level of OHS disclosure, and provides input to the government in formulating policies related to OHS disclosure.